Investigation of adsorption of methylene blue from aqueous phase onto coal-based activated carbons. (19th May 2017) - Purevsuren, B.; Liou, Ya-Hsuan; Davaajav, Ya.; Ariunaa, A.; Batbileg, S.; Avid, B.; Jargalmaa, S.; Huang, Y.; Lin, Chin-Jung
Abstract: We prepared activated carbons (ACs) from coal samples ranking from lignite to anthracite. The pore structures and surface functional groups of the obtained ACs were examined by nitrogen adsorption isotherm, field-emission scanning electron microscopy, Fourier transform infrared spectroscopy, and Boehm's titration method. Isothermal adsorption experiments using methylene blue (MB) solution were conducted to evaluate the adsorption capacities of the ACs. The obtained ACs had different sorption properties due to their differences in structural characteristics and surface chemical groups. The maximum adsorption was achieved using the ACs made from low-ranked lignite coals. The MB adsorption process could be described well by the intra-particle diffusion model with a wide range of effective diffusion coefficients. The results indicated that both the proportion of mesopores and the number of basic sites within the ACs mainly governed the MB adsorption capacities.